2006
DOI: 10.1007/11814764_6
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Coordinates with Backtracking for Void Traversal in Geographic Routing

Abstract: Geographical routing protocols have several desirable features for use in ad hoc and sensor networks but are susceptible to voids and localization errors. Virtual coordinate systems are an alternative solution to geographically based routing protocols that works by overlaying a coordinate system on the sensors relative to well chosen reference points. VC is resilient to localization errors; however, we show that it is vulnerable to different forms of the void problem and have no viable complementary approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 24 publications
0
52
0
Order By: Relevance
“…The paper advocates the use of 3 reference points to assign the virtual coordinates, constructing a 3-dimensional VCS. We showed that this 3D VCS may not sufficient to map the network effectively [23]. VCap, even with 4 coordinates, is worse than GPSR both in delivery ratio (node pair reach-ability) and path quality.…”
Section: Background and Related Workmentioning
confidence: 88%
See 3 more Smart Citations
“…The paper advocates the use of 3 reference points to assign the virtual coordinates, constructing a 3-dimensional VCS. We showed that this 3D VCS may not sufficient to map the network effectively [23]. VCap, even with 4 coordinates, is worse than GPSR both in delivery ratio (node pair reach-ability) and path quality.…”
Section: Background and Related Workmentioning
confidence: 88%
“…In contrast, high density may not resolve the routing anomalies in VCS [23]; it may even exacerbate them due to the quantization noise problems such as VCS forwarding void presented in section III. The complementary solutions for a void avoidance are not effective as described in section II.…”
Section: The Design Of Aligned Vcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Manuel et al [9] have shown that the problem remains NP-complete for bipartite graphs. There are many applications of resolving sets to problems of network discovery and verification [1], pattern recognition, image processing and robot navigation [2], geometrical routing protocols [10], connected joins in graphs [11] and coin weighing problems [12]. This problem has been studied for trees, multi-dimensional grids [2], Petersen graphs [13], torus networks [14], Benes networks [9], honeycomb networks [15], enhanced hypercubes [16] and Illiac networks [17].…”
Section: An Overview Of the Papermentioning
confidence: 99%